The Co-innovation Bingo: An Object-Oriented Networking Mechanism to innovate in Open Innovation Services - Vincent Grèzes; Sandra Grèzes-Bürcher; Riccardo Bonazzi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
In this paper, we describe a business networking tool aiming at fostering collaborative innovation emergence between actors. This tool is designed as a game to encourage participants to share and meet as many partners as possible in a given time. This artefact is based on previous research aiming at identifying collaborative innovation mechanisms and getting inspiration from different fields such as organization design, service design and prospective. The proposed artifact comes as a set of prescriptive rules (Van Aken, 2005) that support managers' co-innovation opportunity elicitation. In preliminary test, 30 exchanges emerged among 20 participants, who did not know each other beforehand. Our contribution is twofold: from a practical point of view, we contribute to help companies to find emergent co-innovation opportunities; and from a theoretical point of view, this artefact is part of our emergent theory of object-oriented co-innovation mechanisms.
Keywords: O36; 330; Collaborative innovation; Coupled innovation; Open innovation; Innovation mechanisms; Design science; Gamification